DISPUTES IN THE PROFESSIONAL ACTIVITY OF A MEDICAL WORKER - Hakimova Xonbuvi; Xudoynazarova Nargiz Yeshkobilovna (Web of Journals Publishing, 2024)
This article explores the challenges and complexities surrounding disputes in the professional activity of medical workers. Focused on understanding the root causes, effective resolution methods, and the impact on patient care, the study delves into the literature, presents empirical data, and discusses implications for healthcare management. The article aims to provide insights for medical professionals, administrators, and policymakers to foster a healthier work environment and enhance the quality of patient care.
Keywords: medical professionals, disputes, conflict resolution, professional ethics, communication, patient care, healthcare management.